Development of Google Sites Web-Based Multimedia Learning in the Arts and Culture Subject for Class X TKJ 2 UPT SMK Negeri 2 Sidenreng Rappang - Aslinda Syamsu; Abd. Kahar; Syamsunir (International Journal of Sustainable Applied Sciences, 2024)
This advancement investigate points to create a item within the shape of Google Destinations Web Learning Mixed media for the Expressions and Culture subject lesson X TKJ 2 UPT SMK Negeri 2 Sidenreng Rappang. The investigate strategy utilized is the Investigate and Advancement (R&D) improvement show with the 4D advancement demonstrate which has been created by Thiagarajan, Semmel and Semmel (1974) which incorporates four stages, to be specific: Characterize which incorporates the beginning last investigation steps, understudy Investigation , concept investigation, and detailing of learning targets; Plan or arranging which incorporates the steps of planning tests, selecting media, selecting instructing fabric groups, and making starting plans; Create or improvement which incorporates item improvement steps, master evaluation, improvement trials, and item modifications. Information collection strategies utilize perception, interviews, surveys and tests which are at that point analyzed quantitatively distinctly; Spread or spread which incorporates the steps of disseminating media. The appraisal comes about appear that the advancement of Google Destinations Web Learning mixed media is evaluated as exceptionally substantial and exceptionally viable. These comes about were gotten from media and fabric master approval, instructor reactions, and reactions from course X TKJ 2 UPT SMK Negeri 2 Sidrap students.